Workers' remittances and import demand in Pakistan - Zaman, Khair-uz; Imrani, Nazakat Ali (2005)
Using quarterly data for the period 1975-2004, this paper estimates import functions for Pakistan both at the aggregate and disaggregated levels. Findings show that remittances do have a significant impact on the demand for imports in the aggregate equation, with the elasticity for remittances being 0.15, and 0.70 for domestically generated income, in the long run (natural logarithm). Remittances, however, have no impact on the demand for imported consumer goods; their impact on the import of raw materials and capital goods are greater than that of domestically generated income.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 137).
Keywords: Migrant remittances -- Pakistan; Imports -- Pakistan